(untitled) (SCIENCE TIME JOURNAL, 2026)
This article provides a systematic analysis of research conducted in world linguistics on astronyms and astronymy. In particular, comparative, linguocultural, ethnolinguistic, and lexicographic studies carried out in Russian linguistics and other languages are examined. The paper also analyzes the role of the anthropocentric approach in the naming of celestial bodies across different languages, the differences between folk and scientific astronyms, and their historical and etymological sources. The article serves as an important scholarly resource for studying the interrelation between language and culture through astronyms.